Introduction to the Special Thematic Issue "Virtual Reality and Eye Tracking" - Béatrice Hasler; Rudolf Groner (Journal of Eye Movement Research)
Technological advancements have made it possible to integrate eye tracking in virtual reality (VR) and augmented reality (AR). Many new VR/AR headsets already include eye tracking as a standard feature. While its application previously has been mostly limited to research, we now see installations of eye tracking into consumer level VR products in entertainment, training, and therapy.